Effect of Microchemistry Elements in Relation of Laser Welding Parameters on the Morphology 304 Stainless Steel Welds Using Response Surface Methodology - Kamel Touileb; Elawady Attia; Rachid Djoudjou; Abdejlil Chihaoui Hedhibi; Abdallah Benselama; Albaijan Ibrahim; Mohamed M. Z. Ahmed (Crystals, 2023)
Small differences in the contents of surface active elements can change flow direction and thus heat transfer, even for different batches of a given alloy. This study aims to determine the effects of sulfur on weld bead morphology in the laser process. The paper presents the results related to the weld bead shape of two thin AISI 304 industrial stainless steel casts. One cast contains 80 ppm (0.008%) of sulfur, considered as a high sulfur content, and the other one contains 30 ppm (0.003%) sulfur, which can be considered low sulfur. The welds were executed using a CO2 laser. The effects of laser power (3.75, 3.67, 6 kW), welding speed (1.25, 2.40, 2.45, 3.6 m/min), focus point position (2, 7, 12 mm), and shield gas (Helium, mixed 40% helium + 60% argon and mixed 70% helium + 30% argon) with a flow rate of 10 L/min on the depth of the weld (D) and the aspect ratio (R = D/W) were investigated using RSM (response surface methodology). The experimental results show that the transfer of energy from the laser beam to the workpiece can be total in cases where the selected welding parameters prevent plasma formation. For the 304 HS cast, the focus point is the major factor in determining the depth of penetration, and its contribution is up to 52.35%. However, for 304 LS, the interaction between shield gas and focus point seems to play an important role, and the contribution of their interaction raises to 28% in relation to the laser depth of the weld. Moreover, the study shows that sulfur plays a surface-active role only in the case of partial penetration beads, so that a 56% partially penetrated weld supports the hypothesis of its surface-active role in the formation of the weld pool. However, a penetration of only 36% confirms the effects of a sulfur surface-active when the bead is fully penetrated.